Hubungan Pengetahuan, Persepsi, Self Efficacy dan Pengaruh Interpersonal Terhadap Pencegahan Penularan TB Paru di Puskesmas Muara Kumpeh Kabupaten Muaro Jambi Tahun 2016 - dian octavia (Riset Informasi Kesehatan, 2017)
Abstract The Primary Health Center Muara Kumpeh was shown that patients with pulmonary TB were growing up for every single year. The data in 2014 was shown for 44 cases totally and increased in 2015 as many as 54 cases. The knowledge has been a role in a person's perception.One's knowledge is the beginning of a behavioral factor that correlates positively with actions to prevent transmission of pulmonary TB. This research is a quantitative research with cross sectional study design. The goal is to determine the relationship of knowledge, perception, self-efficacy, and interpersonal influences on the prevention of pulmonary TB transmission in the region Muara Kumpeh Primary Health Center 2016. The sample of this study was 54 peoples and was using a Total Sampling Technique. This study in April 2016, analyzed using univariate and bivariate with a Chi-Square test. The results of the study indicated that there has a relationship between of knowledge with p = 0.038, the perceptions of the value of p = 0.000, self-efficacy (confidences) with a value of p = 0.003, and interpersonal influences with p = 0.047. The total of 30 (55.6%) of respondents has good Prevention's and 24 (44.4%) of respondents were less good at preventing transmission of pulmonary TB. This research was found that all of the variables have a significant relationship with the prevention of transmission of Lung’s TB with p-value <0, 05. The health workers should make a therapeutic relationship more to the patients so that the respondents were more feels comfortable and open to the questions, on the complaint of their illness, a language should be easy to understand by the respondent. The message was real to put women more aware of the importance of healing and a better understanding of what that should be done in the prevention of Lung’s TB to other families member.